SYNTAX score II in patients with coronary artery disease undergoing percutaneous mitral repair with the MitraClip. (1st June 2017) - Obeid, Slayman; Attinger-Toller, Adrian; Taramasso, Maurizio; Pedrazzini, Giovanni; Suetsch, Gabor; Landolt, Fabienne; Karbeyaz, Fatih; Rodriguez, Hector; Sürder, Daniel; Moccetti, Tiziano; Nietlispach, Fabian; Maisano, Francesco
Abstract: Background: Percutaneous mitral valve repair (PMVR) using the MitraClip™ system has become a valuable alternative in patients with severe mitral regurgitation (MR) and high surgical risk. We sought to evaluate the prognostic value of the SYNTAX II score (SSII) in patients with concomitant coronary artery disease (CAD) undergoing a Mitraclip procedure. Methods: In seventy-five consecutive patients who underwent PMVR at the University Heart Center Zürich and the Cardiocentro Ticino, the SSSII was calculated at baseline. Clinical endpoints comprised of all-cause mortality, mitral valve surgery due to failure of PMVR or reoperation, hospitalization for congestive heart failure, heart transplantation and the composite of all four endpoints. Results: Patients were followed for a median of 271 days. And were divided in tertiles of SSII: SSII low ≤ 46.5 ( n = 25), SSII mid 46.6–54.4 ( n = 25) and SSII high ≥ 54.5 ( n = 25). Patients in the highest SSII tertile had a lower left ventricular ejection fraction (33% vs. 40% vs. 53%) with a higher log-BNP (3.6 vs. 3.45 vs. 3.16) when compared to SSII mid and SSII low, respectively. However, the anatomical syntax score (SS) did not differ significantly within the tertiles (9.1 ± 6.3 (SSII Low) vs 9.5 ± 7.6 (SSII Mid) vs 10.2 ± 6.7(SSII High), p = 0.837). The primary endpoint occurred in 33% of patients ( n = 25). By multivariate analysis patients in the high SSII tertile (OR = 6.12, 95% confidence interval, [CI] 1.45–25.86, p = 0.014) and patients with a history of MI (OR = 3.57, 95% confidence interval, [CI] 1.17–10.88, p = 0.025) were at significantly higher risk of experiencing adverse events. Furthermore, in a combined outcome ROC curve analysis, the SSII showed good discrimination with an AUC of 0.73, p = 0.001. A cutoff SSII > 49 has been identified to have a sensitivity of 83% and specificity of 53% with approximately 45% of the patients experiencing an event during follow-up. Conclusion: Using SSII in CAD patients undergoing PMVR is feasible and of prognostic significance hence widening its clinical utility in valvular heart disease.